Модель рентгеновской поликапиллярной линзы в приближении геометрической оптики - Углов С. Р. Сергей Романович; Филатов Н. А. Николай Александрович; Чистяков С. Г. Сергей Геннадьевич; Гоголев А. С. Алексей Сергеевич; Казарян М. А. Мишик Айразатович; Обходский А. В. Артем Викторович (2018, 2018)
Заглавие с экрана